PERANCANGAN SISTEM INFORMASI MONITORING PROGRAM KERJA DESA PADA DESA CIKAKAK - Vannesa Adenia Wilmar (2021)
This village work program monitoring system can provide convenience for village staff in providing monitoring reports on conducting of the work programs, so they no longer carry out manual recordings which can pose a risk of data loss and inaccurate data. By using this monitoring system, the recording of data related to the village work program is also stored neatly into the database. The purpose of this research is to design an information system for monitoring village work programs in Desa Cikakak using the waterfall method with the laravel framework which the database server is using MySQL. With this village work program monitoring system (SIMPROKDES) it is hoped that the writer can meet the needs of the staff and facilitate the work the village stakeholders so that everything becomes more efficient.